Application of airborne laser scanning data for the identification of landslide areas - Pawłuszek Kamila (Wykorzystanie danych lotniczego skaningu laserowego w identyfikacji obszarów osuwiskowych, 2019)
The purpose of the research presented in this work is the application of ALS data for the identification of landslide areas. The thesis presents three main application trends of ALS data used in the landslide context namely: (1) identification of existing landslides, (2) identification of characteristic landslide forms and morphology and (3) identification of areas susceptible to landslides. For this purpose, ALS data is used to generate DEM and an extended set of DEM derivatives. This wide set of DEM derivatives was a fundamental source to develop methodologies for the automatic identification of landslides, their characteristic forms and the landslide susceptibility assessment.
W wersji elektronicznej dostępne wyłącznie streszczenie rozprawy doktorskiej
Keywords: osuwiska; skaning laserowy; podatność osuwiskowa; identyfikacja osuwisk; modelowanie podatności osuwiskowej; formy osuwiskowe